Protein-linked glycans in periodontal bacteria: prevalence and role at the immune interface - Settem, Rajendra P.; Honma, Kiyonobu; Stafford, Graham P.; Sharma, Ashu (Frontiers in Microbiology, 2013)
Protein modification with complex glycans is increasingly being recognized in many pathogenic and non-pathogenic bacteria, and is now thought to be central to the successful life-style of those species in their respective hosts. This review aims to convey current knowledge on the extent of protein glycosylation in periodontal pathogenic bacteria and its role in the modulation of the host immune responses. The available data show that surface glycans of periodontal bacteria orchestrate dendritic cell cytokine responses to drive T cell immunity in ways that facilitate bacterial persistence in the host and induce periodontal inflammation. In addition, surface glycans may help certain periodontal bacteria protect against serum complement attack or help them escape immune detection through glycomimicry. In this review we will focus mainly on the generalized S-layer protein glycosylation system of the periodontal pathogen Tannerella forsythia in shaping innate and adaptive host immunity in the context of periodontal disease. In addition, we will also review the current state of knowledge of surface protein glycosylation and its potential for immune modulation in other periodontal pathogens.